The Function of the Delimitation Contradictory Principle in the Settlement of Land Plot Boundary Disputes - Rahmat Ramadhani; Ummi Salamah Lubis (International Journal Reglement & Society (IJRS), 2021)
Placement of boundaries is necessary to avoid boundary disputes between landowners. The installation of land boundary markings by the owner with the approval of the boundary neighbors witnessed by village officials or authorized officials is called the delimitation contradiction principle. This principle is evidenced by an affidavit of approval which is signed directly by the land owner and adjacent land owner and witnesses who are present in the form of village officials. The principle of contradictory delimitation is a very basic thing that must be done by the owners, this is the main and very important condition for the land to be registered at the land office. Although land registration and the principles in land registration have been regulated in such a way and there is a legal basis governing these provisions, there are still many people who do not care, causing a problem, one of which often occurs in the field, namely the lost land boundary because the owner does not care. maintain and maintain these boundaries properly so that at the time of measurement by the land surveying officer, new land boundaries are installed and do not present bordering neighbors so that errors can occur in determining land boundaries. The problem that often arises is that neighboring neighbors underestimate their presence, consider measurements to be unimportant for certain reasons and because this can lead to disputes with other owners seizing land boundaries and there is no agreement between the parties in determining land boundaries. This indicates that the delimitation contradiction principle is not fulfilled. The procedure used to collect data in this study is in the form of documentation, namely the guidelines used in the form of notes or quotes, searching for legal literature, books and others related to the identification of problems in this study both offline and online. Analysis of legal materials is carried out using the content analysis method which is carried out by describing the material of legal events or legal products in detail in order to facilitate interpretation in the discussion. Basically the application of the delimitation contradiction principle is the presence of the parties concerned, namely the land registration applicant and the parties directly adjacent to the land boundary measurement and mapping carried out by the Land Office. has not been carried out, it is also possible that all of the parties concerned came but at the time of the measurement there was a dispute of opinion regarding the results of the measurement and mapping of land boundaries that was carried out, the application of the Delimitation Contradictory principle had also not been implemented.